Hubungan Asupan Gizi Anak Terhadap Stunting Pada Balita 3-5 Tahun - Dian Nawang Wulan; Novi Puspita Sari; Putu Intan Yunita Dewi; Putu Krisna Dewiyani Hantana; Siti Nur Khazanah; Didik Sarudji (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2022)
Stunting is a chronic malnutrition problem caused by lack of nutritional intake for a long time, resulting in growth disorders in children, namely the child's height is lower or shorter (short) than the standard age. Based on the results of basic health research (Riskesdas) in 2018, the percentage of stunting in children under five decreased by 30.8% with a percentage of 19.3% of short children and 11.5% of very short children. In East Java alone, the percentage of stunting is around 32%. Meanwhile, in Mojokerto alone, the stunting rate reachedaround 30.5%. Therefore, this study aims to analyze whether there is a relationship between children's nutritional intake and the incidence of stunting at the Puskesmas Gedeg. Where the independent variable in this study is the nutritional intake of children and the dependent variable is the incidence of stunting in toddlers. The design in this study was case control and the population was all children aged 3-5 years in the working area of the Puskesmas Gedeg, Gedeg District, Mojokerto Regency with a totalsample of 90 children under five. The data from this study were processed using the Chi-square statistical test which was then followed by the Odds Ratio test. And from the results of the study, it was found that there was a relationship between risk factors for nutritional intake of children aged 3-5 years and the incidence of stunting at the Puskesmas Gedeg, Gedeg District, Mojokerto Regency.